اخفاء معلومات في تعليمة المحتويات للملف الصوتي MP3 Information hiding using IDv3 tag in MP3 file - عبد، سعد حميد (كلية المنصور الجامعة, 2009)
أن إخفاء المعلومات انتشر في الآونة الأخيرة على مدي واسع وبمختلف الطرق والأساليب والذي بدوره يستخدم لإخفاء بيانات داخل الأوساط المتعددة وتطبيقاتها لأمنية الأوساط المتعددة، وبعبارة أخري هو عملية إخفاء معلومة معينة داخل وسط معين كصورة أو صوت أو حتى ملف نص بسيط. في هذا البحث سوف نستخدم طريقة جديدة لإخفاء المعلومات داخل الملفات الصوتية من نوع Mp3وبدل استخدام الطريقة التقليدية التي تقوم بإخفاء المعلومات داخل بيانات الصوت نفسها سوف نقوم بأخفاء المعلومات داخل حيز يدعي ب ID3 tag والمخصص للاحتفاظ بمعلومات تخص ماهية الملف الصوتي وليس معلومات الصوت نفسها. As we all know that digital information hiding (or steganography) is used to embed data (information) into digital media for the purpose of identification, annotation, and copyright. In other words it is the operation of hiding certain information into a specific cover media such as pictures and audio files or even in a simple text files. In this paper a new approach in hiding information into an MP3 file was proposed, simply instead of using the traditional method of hiding into the actual audio data we will hide our secret messages into the IDv3 tag which is a tag used to store specific information about the MP3 file. The IDv3 tag has gone into a several changes to reach its current version (version 3) containing several interesting features that will be used as a cover for our secret message, first of all a simple overview for the versions and releases of the ID tag is illustrated and display the features of the IDv3 tag which we will use as a cover media.
ملخص لبحث منشور باللغة الانجليزية
Keywords: مستخلصات الابحاث -- اخفاء المعلومات -- الوسائط المتعددة -- التطبيقات الامنية -- الملفات الصوتية MP3